2020
DOI: 10.1007/s12649-020-01176-1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Agriculture Residues Pretreatment Using Deep Eutectic Solvents

Abstract: The purpose of this work is to investigate a new class of solvents for separating secondary agricultural residues, which have already been transported to processing centers, into individual biomass components. Using biocompatible deep eutectic solvents (DES) on secondary agricultural residues could valorize these wastes into bioproducts by separating lignin from cellulose. DES pretreatment to achieve this separation involves chemicals that are less hazardous for the environment than other pretreatments. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…10 Choline chloride-carboxylic acid DESs have the characteristics of low cost, high boiling point, easy preparation, environmental friendliness, and designable structure, and have attracted much attention as a good medium for lignocellulose pretreatment, 11 dearomatization of gasoline, 12 battery recycling 13 etc. For example, Kumer et al 14,15 found that both ChCl/formic acid (FA) and ChCl/ acetic acid (AA) were effective in lignin separation from biomass rice hull and sugarcane bagasse. The choline chloride-carboxylic acid DESs can preferentially dissolve lignin at 60 1C and are stable at 100-160 1C.…”
Section: Introductionmentioning
confidence: 99%
“…10 Choline chloride-carboxylic acid DESs have the characteristics of low cost, high boiling point, easy preparation, environmental friendliness, and designable structure, and have attracted much attention as a good medium for lignocellulose pretreatment, 11 dearomatization of gasoline, 12 battery recycling 13 etc. For example, Kumer et al 14,15 found that both ChCl/formic acid (FA) and ChCl/ acetic acid (AA) were effective in lignin separation from biomass rice hull and sugarcane bagasse. The choline chloride-carboxylic acid DESs can preferentially dissolve lignin at 60 1C and are stable at 100-160 1C.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose content at the delignification ratio of 1:4 and 1:6 for 2 h increased compared to the initial coconut husk samples. According to [49], delignifi-cation can increase glucose content due to an increase in cellulose accessibility due to the removal of hemicellulose and lignin content. DES and NADES solvents broke down the lignin bond from lignocellulose and diluted it to wash water after the delignification process.…”
Section: Effect Of the Delignification Process On Glucose Contentsmentioning
confidence: 99%
“…Dried and sieved biomass of a mass of 3 g was mixed with 30 g of each of the three types of DES: FA:CC (2:1 ratio), LA:CC (10:1 ratio), AA:CC (2:1 ratio) in separate flasks with a magnetic stirrer for continuous stirring and kept in the preheated oil bath for 1 h at 125 • C. Time and temperature were chosen as the minima found to be effective in prior work [12]. The flask with this solution mixture was connected to a condenser to collect liquid from the vapor of the slightly volatile DES in order to maintain the solvent volume constant.…”
Section: Pretreatment Of Pine Needles Using Desmentioning
confidence: 99%
“…A visual inspection of the pine needles treated with FA:CC and LA:CC appeared to show a greater extent of biomass breakdown compared to AA:CC. FA:CC pretreatment may be more effective because it has a lower pKa value than the other DES [12].…”
Section: Mass Yield From Deep Eutectic Solvents (Des) Pretreatmentmentioning
confidence: 99%